The Effects of Physical Activity Numeracy, BMI Literacy, and Health Statistical Reasoning on Physical Fitness among Physical Education Students - Suharti; Hendra Setyawan; Lalu Moh Yudha Isnaini; Sabariah; Eka Kurnia Darisman; Mulyono; Henri Gunawan Pratama (Jurnal Penelitian Pendidikan IPA, 2026)
Declining physical activity and lifestyle changes among physical education students may reduce physical fitness, while professional demands require them to design data-informed exercise programmes. This study aimed to analyses the effects of physical activity numeracy ability, BMI literacy, and health statistical reasoning on physical fitness among physical education students. Quantitative correlational survey design was employed. The sample comprised 133 physical education students selected purposively. Data were collected using four-point Likert-scale questionnaires, each consisting of 16 items for physical activity numeracy, BMI literacy, health statistical reasoning, and physical fitness. Item validity was examined using Pearson correlation analysis, showing that all items were valid with item–total coefficients above the critical r value, whereas Cronbach’s alpha coefficients ranged from 0.945 to 0.967. Data were analyzed using descriptive statistics, Pearson correlations, and multiple linear regression, preceded by classical assumption tests. The regression model was significant (R² = 0.573; p < 0.001). Partially, physical activity numeracy (β = 0.504; p < 0.001) and health statistical reasoning (β = 0.284; p = 0.031) had positive and significant effects on physical fitness, whereas BMI literacy showed no significant effect (β = −0.006; p = 0.956). These findings highlight the importance of reinforcing exercise numeracy and health statistical reasoning in physical education curricula to support the design, monitoring, and evaluation of evidence-based exercise programmes, thereby enhancing students’ physical fitness and their readiness as future PE teachers. Longitudinal and structural modelling studies are recommended to minimise multicollinearity and test mediation mechanisms among variables in Indonesian higher education settings.